If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2 + -4x + -3 = 11 Reorder the terms: -2 + -3 + 8x + -4x = 11 Combine like terms: -2 + -3 = -5 -5 + 8x + -4x = 11 Combine like terms: 8x + -4x = 4x -5 + 4x = 11 Solving -5 + 4x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4x = 11 + 5 Combine like terms: -5 + 5 = 0 0 + 4x = 11 + 5 4x = 11 + 5 Combine like terms: 11 + 5 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| D+32=97 | | b-23=(1/2)b+27 | | 4(3x-5)=-2(x+7) | | 15.50+0.50=x | | (3-3i)+(7+6i)=0 | | b-23=1/2b+27 | | -4x^2-x=6 | | 3*7+5y=-14 | | -2x-2=-4-8x+6x+2 | | x+6=60x | | 4(0.125t+2)=2(t-8)-0.5t | | W=Y(b+R)findb | | In(x+1)+In(x-1)=4 | | log(5)(11-4x)=3 | | 4x^2+13=-5 | | 3x+11=5x+12 | | 4y-7+4y-7=90 | | 10y-12=5(2y+3)-y | | 9x+4y=-84 | | 2x+2(4x-2)=35 | | 2x^2-4x-3y=1 | | -5x+3y=-16 | | -3k+2=41 | | Z^2-15z+44=0 | | 3x^3+6x^2+3x=0 | | 4(7x-8+6)=19+3 | | x^3+1x^2-2x+168= | | 2(3a-a)=18 | | 20+.15x=30+.10y | | 0.2(z+12)=0.4(9-3z) | | -7(-3-2x)=-49 | | 12-15=7d+85 |